2019
DOI: 10.1136/bmjoq-2019-000686
|View full text |Cite
|
Sign up to set email alerts
|

Exploring stakeholder perceptions around implementation of the Operating Room Black Box for patient safety research: a qualitative study using the theoretical domains framework

Abstract: BackgroundSystematically observing clinical performance in the operating room (OR) to support patient safety initiatives faces numerous logistical and methodological challenges. These may be solved by new audio-video recording technologies like the OR Black Box, which is a tool similar to black boxes in aviation. This study aimed to identify barriers and enablers that may influence patients’, clinicians’ and senior leadership team members’ support of the OR Black Box in order to guide its future implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 26 publications
4
31
0
Order By: Relevance
“…Our qualitative study of stakeholder perceptions regarding the Operating Room Black Box was approved by the OHSN-REB, Protocol #20170117-01H. This study was reported separately elsewhere [ 28 ]. In short, interviews were conducted with 15 patients across 3 hospital campuses (5 patients each), 17 perioperative clinicians, and 9 hospital administrators.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our qualitative study of stakeholder perceptions regarding the Operating Room Black Box was approved by the OHSN-REB, Protocol #20170117-01H. This study was reported separately elsewhere [ 28 ]. In short, interviews were conducted with 15 patients across 3 hospital campuses (5 patients each), 17 perioperative clinicians, and 9 hospital administrators.…”
Section: Resultsmentioning
confidence: 99%
“…A full description of the methodology has been published elsewhere [ 28 ]. Briefly, participants were recruited across each of the 3 campuses of our center, either in-person (patients) or via email (clinicians and administrators).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33] The only other published qualitative study of the video review technology to date was conducted by Etherington et al on the implementation of the operating room (OR) "Black Box" in Ottawa, Ontario. 34 They also found that while most stakeholders were supportive of the OR Black Box and would agree to be recorded, there are many areas that need to be addressed including ensuring all stakeholders have adequate and accurate information about the OR Black Box system and research goals and that the OR Black Box is positioned as a patient safety initiative for learning from and improving everyday practice across the whole team.…”
Section: Discussionmentioning
confidence: 99%
“…28 In general, whereas patients were as a whole supportive and comfortable by its use in the operating room, physicians were more concerned about the consent process, security, and medicolegal issues. 29,30 Ultimately, surgical data recording technologies vary in the amount and types of data collected, degree of technology integration, and related utility in the clinical setting. However, because data recording technologies may capture audio, video, patient, and provider data associated with sensitive protected health information, they inherently carry medicolegal questions.…”
Section: Legal and Regulatory Consideration For Black Box Usementioning
confidence: 99%